The perceived impact of a relative's mental illness on the family members, their reported coping strategies and needs : a Zimbabwean study - Marimbe-Dube, Bazondile (Centre for Public Mental Health, 2014)
Aim of the study is to explore the perceived impact of mental illness, reported coping strategies and reported needs of family members of mentally ill patients attending the Parirenyatwa Annexe Psychiatry Unit in Harare, Zimbabwe.